2020
DOI: 10.1007/jhep04(2020)084
|View full text |Cite
|
Sign up to set email alerts
|

$$ T\overline{T} $$ deformed CFT as a non-critical string

Abstract: We present a new exact treatment of TT deformed 2D CFT in terms of the worldsheet theory of a non-critical string. The transverse dimensions of the non-critical string are represented by the undeformed CFT, while the two longitudinal light-cone directions are described by two scalar fields X + and X − with free field OPE's but with a modified stress tensor, arranged so that the total central charge adds up to 26. The relation between our X ± field variables and 2D dilaton gravity is indicated. We compute the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 33 publications
2
73
0
Order By: Relevance
“…The closed worldline thus becomes an open one with "boundary" states jX 1 i and jX 2 i at its ends. This is similar to the D-brane boundary condition proposed for TT deformed 2d conformal field theory (CFTs) in [28]. The path integral we then wish to compute is a transition amplitude:…”
Section: A Worldline Gravity Picture For Correlatorsmentioning
confidence: 82%
See 1 more Smart Citation
“…The closed worldline thus becomes an open one with "boundary" states jX 1 i and jX 2 i at its ends. This is similar to the D-brane boundary condition proposed for TT deformed 2d conformal field theory (CFTs) in [28]. The path integral we then wish to compute is a transition amplitude:…”
Section: A Worldline Gravity Picture For Correlatorsmentioning
confidence: 82%
“…By coupling the undeformed theory to a theory of one-dimensional gravity and performing the path integral over all fields, we showed that the thermal partition function is precisely reproduced. This is analogous to the description of the TT deformation of two-dimensional theories as coupling to JT gravity or 2d non-critical string theory [26][27][28].…”
Section: A Worldline Gravity Picture For Correlatorsmentioning
confidence: 87%
“…These include the TT deformations and their higher-spin generalizations [57][58][59], the JT /TJ deformations in theories with a conserved U(1) current [60,61], and their linear combinations [62][63][64]. These deformations enjoy remarkable properties including closed formulae for the deformed spectrum, modular invariance (TT ) or covariance (JT /TJ) of the torus partition functions [65][66][67][68][69], as well as connections to strings and 2d gravity [59,[70][71][72][73][74][75][76][77][78]. The holographic interpretation of these irrelevant deformations include the double-trace version which changes the boundary conditions but does not change the local bulk geometry [79][80][81], as well as a single-trace version which also changes the local geome-…”
Section: Introductionmentioning
confidence: 99%
“…Since our analyses in this note are purely based on equation of motion, it is possible that this chiral decoupling doesn't persist when quantum corrections are considered. It would be interesting to study the corresponding quantum field theories, perhaps along the lines of [9,35]. We hope to return to these questions in the near future.…”
Section: Fermionsmentioning
confidence: 99%